The interaction of clumping factor B and iron-regulated surface determinant protein A of Staphylococcus aureus with the squamous epithelial cell envelope protein loricrin - Mulcahy, Michelle (Trinity College (Dublin, Ireland). Department of Microbiology, 2013)
Staphylococcus aureus permanently colonises the anterior nares of 20% of the human population while the remainder is colonised intermittently. Clumping factor B (ClfB) is a surface-expressed staphylococcal protein that plays a role in nasal colonisation. ClfB promotes bacterial adherence to human desquamated epithelial cells (squames) and ClfB-deficient strains of S. aureus displayed a significantly reduced ability to colonise the nares of rodents and healthy human volunteers. The iron-regulated surface determinant protein A (IsdA) is also involved in nasal colonisation. IsdA promotes bacterial adherence to squames and an interaction between IsdA and loricrin has been suggested. ClfB binds to the aC-region of fibrinogen and to the tail region of the surface- exposed squamous cell protein cytokeratin 10 (K10). The ClfB-binding site within K10 was localised to the glycine serine-rich omega loops in the K10 tail. Unpublished evidence from E. Walsh and T.J. Foster suggested that ClfB binds to loricrin, another structural protein present in the cornified envelope.
Keywords: Microbiology, Ph.D.; Ph.D. Trinity College Dublin